Predictors of AI awareness among EFL learners: gender, English proficiency, ICT usage, and the personality traits - Genç, Gülten; Rıhawi, İbrahim (Frontiers in Education, 2026)
This study examined English as a Foreign Language (EFL) learners’ awareness of artificial intelligence (AI) and its associations with gender, Big Five personality traits, self-assessed English proficiency, and information and communication technology (ICT) usage. A quantitative, cross-sectional survey design was employed, and participants were selected through convenience sampling. Data were collected from 155 EFL university students at a public university in Türkiye during the spring semester of 2024. Statistical analyses were performed using SPSS Version 26.0. A K-means cluster analysis identified two distinct personality profiles–Introverted–Neurotic and Open–Extraverted. A multivariate analysis of variance (MANOVA) was then conducted to examine whether gender, personality profile, English proficiency, and ICT usage predicted differences across four dimensions of AI awareness: Basic Knowledge, Benefit, Bias, and Negative Forecast. No statistically significant differences emerged across demographic or personality factors, suggesting a relatively homogeneous level of AI awareness among EFL learners. Stepwise regression analyses revealed that Openness and Extraversion were significant predictors of overall AI awareness. These findings indicate that personality characteristics–particularly openness to experience–play a meaningful role in shaping learners’ engagement with AI technologies in language education.